Influence of Planting Depth and Application Timing on S-metolachlor Injury in Sesame (Sesamum indicum L.). (December 2016) - Sperry, Benjamin P.; Ferrell, Jason A.; Leon, Ramon G.; Rowland, Diane L.; Mulvaney, Michael J.
Abstract : Two experiments were conducted in 2015 at multiple locations in Florida to evaluate the effects of planting depth and application timing on S -metolachlor injury in sesame. In both studies, sesame responded negatively to increases in S -metolachlor rate. Altering sesame planting depth did not provide increased safety to PRE S -metolachlor applications. Sesame establishment declined with increased planting depth, likely because of the physical inability of the small seed to emerge from the 3.8-cm depth. Delaying applications of S -metolachlor by 3 or 6 d after planting (DAP) consistently improved sesame establishment. Applications 3 and 6 DAP resulted in 89 to 92% seedling emergence at 2 wk after planting (WAP), relative to 55 to 63% emergence when S -metolachlor was applied the day of planting (0 DAP) or 3 days before (−3 DAP), respectively. Applications 3 DAP resulted in 21 and 2% plant stunting when evaluated 3 and 6 WAP, respectively, whereas all other timings caused 25 to 51% stunting. Yield was reduced 22 and 33% by the −3 DAP and 0 DAP application timings, respectively, whereas no reduction in yield was observed by the delayed application timings. Therefore, delaying applications of S -metolachlor by 3 to 6 days will likely result in improved sesame seedling establishment and total seed yield.